Cultural Diplomacy of China towards Thailand through the Confucius Institutes - Imcharoen, Sudaporn; Klaitabtim, Juthatip (Connexion: Journal of Humanities and Social Sciences, 2023)
The objectives of this research were to identify the operations and role of Confucius Institutes in Thailand, and to analyze the impact of cultural diplomacy of China on Thailand through the Confucius Institutes. This study was qualitative research, employing documentary research and in-depth interviews. The results of the research showed that the main aims of the Confucius Institutes in Thailand are to enhance increased understanding of Chinese language and culture, promote educational and culture exchanges, and develop cooperation between Thailand and China in various dimensions. In addition, the Confucius Institutes have expanded its scope of implementation to jointly develop manpower capability in Chinese language and vocational skills for the industrial sector. Since the inception the Confucius Institutes in 2006, China’s use of this soft power in driving cultural diplomacy policy through Chinese language and culture education has clearly benefited Thai society. The crucial impacts were the development of teaching and learning Chinese language in Thailand, opportunity creation for learning Chinese language, and the closer relationship and cooperation among agencies of the two countries. At present, Thailand and China have elevated their existing educational cooperation to further improve the quality of Chinese language and culture instruction.